Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Karyawan Pada PT. Murfa Surya Mahardika Makassar - Nuraini Nafisha N Junus; Anwar; Agung Widhi Kurniawan; Amiruddin Tawe; Rezky Amalia Hamka (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
This study aims to determine the extent of the influence of workload and work stress on employee performance at PT Murfa Surya Mahardika Makassar. This research is quantitative in nature using an associative approach. The population of this study consisted of 32 employees of PT Murfa Surya Mahardika Makassar. The sample used in this study was a saturated sample, so the entire population was used as a sample. Based on the results of hypothesis testing, it is found that the workload variable (X1) has a positive and significant effect partially on employee performance (Y). The work stress variable (X2) has a partially negative and significant effect on employee performance (Y). Workload variables (X1) and work stress (X2) have a simultaneous positive and significant effect on employee performance (Y), which affects employee performance by 51.2% with other variables not studied affecting the remaining 48.8%.